Magnetic Anisotropy in "Scorpionate" First‐Row Transition‐Metal Complexes: A Theoretical Investigation. Issue 9 (15th January 2015) - Perić, Marko; García‐Fuente, Amador; Zlatar, Matija; Daul, Claude; Stepanović, Stepan; García‐Fernández, Pablo; Gruden‐Pavlović, Maja
Abstract In this work we have analyzed in detail the magnetic anisotropy in a series of hydrotris(pyrazolyl)borate (Tp−) metal complexes, namely [VTpCl]+, [CrTpCl]+, [MnTpCl]+, [FeTpCl], [CoTpCl], and [NiTpCl], and their substituted methyl and tert‐butyl analogues with the goal of observing the effect of the ligand field on the magnetic properties. In the [VTpCl]+, [CrTpCl]+, [CoTpCl], and [NiTpCl] complexes, the magnetic anisotropy arises as a consequence of out‐of‐state spin–orbit coupling, and covalent changes induced by the substitution of hydrogen atoms on the pyrazolyl rings does not lead to drastic changes in the magnetic anisotropy. On the other hand, much larger magnetic anisotropies were predicted in complexes displaying a degenerate ground state, namely [MnTpCl]+ and [FeTpCl], due to in‐state spin–orbit coupling. The anisotropy in these systems was shown to be very sensitive to perturbations, for example, chemical substitution and distortions due to the Jahn–Teller effect. We found that by substituting the hydrogen atoms in [MnTpCl]+ and [FeTpCl] by methyl and tert‐butyl groups, certain covalent contributions to the magnetic anisotropy energy (MAE) could be controlled, thereby achieving higher values. Moreover, we showed that the selection of ion has important consequences for the symmetry of the ground spin–orbit term, opening the possibility of achieving zero magnetic tunneling even in non‐Kramers ions. We have also shown that substitution may also contribute to a quenching of the Jahn–Teller effect, which could significantly reduce the magnetic anisotropy of the complexes studied.